An efficient mathematical model for the Outbreak of COVID-19from the perspective of numerical analysis - Gholami, Hossein; Gachpazan, Mortaza; Erfanian, Majid (Iraqi Journal of Science, 2025)
In this paper, we developed an  epidemic model for COVID-19 by using compartmental analysis. In our model, we divided susceptible individuals into two separate groups: one for high-risk individuals and another for those at low risk. In this work, we have proved theorems about the non-negativity and boundedness of the solutions. Afterward, we obtained a disease-free equilibrium point and an endemic equilibrium point. We calculated the basic reproduction number using the next-generation matrix method and then we expressed theorems about the local and global stability of equilibria, finally, we have gone to the sensitivity analysis and numerical analysis.